2013
DOI: 10.1161/jaha.112.004531
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity and Blood Pressure Control in 37 651 Hypertensive Patients From Danish General Practice

Abstract: BackgroundPatients with hypertension are primarily treated in general practice. However, major studies of patients with hypertension are rarely based on populations from primary care. Knowledge of blood pressure (BP) control rates in patients with diabetes and/or cardiovascular diseases (CVDs), who have additional comorbidities, is lacking. We aimed to investigate the association of comorbidities with BP control using a large cohort of hypertensive patients from primary care practices.Methods and ResultsUsing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 35 publications
2
31
2
1
Order By: Relevance
“…To the best of our knowledge, only one study compared the estimated cardiovascular risk between hypertensive men and women and reported similar findings . Despite the higher estimated risk in women, the prevalence of established CVD did not differ between sexes, in contrast with previous reports, which reported higher rates in men . A possible explanation for this finding is that the Framingham equation underestimates the cardiovascular risk in women .…”
Section: Discussionmentioning
confidence: 53%
“…To the best of our knowledge, only one study compared the estimated cardiovascular risk between hypertensive men and women and reported similar findings . Despite the higher estimated risk in women, the prevalence of established CVD did not differ between sexes, in contrast with previous reports, which reported higher rates in men . A possible explanation for this finding is that the Framingham equation underestimates the cardiovascular risk in women .…”
Section: Discussionmentioning
confidence: 53%
“…Such a database is under development and implementation thus allowing for a reasonable level of qualification of such prescriptions on a nationwide basis in the future. 19,20 in the European Surveillance of antimicrobial Consumption study, the total (including adults) use of outpatient antibiotics in Denmark was low (about 14 DDD per 1000 inhabitants daily) compared with most other countries, 3 and the described utilization may be viewed as an example of a relatively low prescription rate pattern.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the finding that morbidity count was associated with poorer BP control was consistent with a previous study. [24] However, the same study also postulated that multimorbidity could result in more frequent contacts with medical practitioners, and thus facilitated their BP control. [24] Having diabetes mellitus as a comorbidity should be regarded as an exceptional case since the threshold of optimal control is different and harder to achieve (<130/90 mmHg).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…A previous study, however, indicated that some comorbidity might improve BP control while some might hinder it. [24] Each comorbidity as a separate covariate could be investigated in future research to explore this relationship in greater depths. In addition, the variables studied were mostly socioeconomic factors, patient-related factors and therapy-related factors.…”
Section: Accepted Manuscriptmentioning
confidence: 99%